Analysis of Internal and External Motivation with Breast Self-Examination in Breast Cancer Prevention - Azurah, Nindy; Nurwijayanti (Universitas STRADA Indonesia, 2020)
Cancer is one of the main causes of death, and the most common type of cancer in women is breast cancer. Early detection of breast cancer is an attempt to detect or identify early breast cancer. Breast self-examination is one way to do early detection of breast cancer. The aim of this study was to analyze internal and external motivation with breast self-examination in breast cancer preventionThe design of this research is quantitative descriptive with cross sectional approach with the focus of the research being directed to analyze internal and external motivation with breast self-examination in breast cancer prevention by taking a sample of 96 respondents and the data analysis used is linear regression.The findings showed that most of the respondents already had internal motivation to prevent breast cancer as many as 24 respondents and those who had external motivation to prevent breast cancer were as many as 57 respondents, but 50 respondents had not routinely performed their own breast examinations, 52%. The results of the study using the Linear Regression Test showed that the value of F count = 32.4 with a significance level of 0.000 <0.05, so H1 is accepted, so it can be concluded that there is an influence of internal and external motivation with breast self-examination in breast cancer prevention.The community already has the motivation to prevent breast cancer but it cannot be practiced regularly and this needs to increase public awareness to be more routine in breast self-examination.